Cat on a hot tin roof [videorecording (DVD)] - Brooks, Richard, 1912-1992; Taylor, Elizabeth, 1932-2011; Newman, Paul, 1925-2008; Ives, Burl, 1909-1995; Williams, Tennessee, 1911-1983 (Turner Entertainment : Warner Bros. Entertainment, 2006)
A story of deception which is destroying a patriarchal Southern family as its members gather for the imminent demise of their "Big Daddy."